Cross-Border Cargo Traffic Through a Rural Texas Port of Entry - Fullerton, Jr., Thomas M.; Fullerton, Steven L. (Journal of Applied Business and Economics, 2022)
Most econometric analyses of cross-border traffic flows from Mexico have been conducted for the larger metropolitan economies along the international boundary. With the advent of the USMCA trade agreement, plus physical infrastructure bottlenecks at many ports of entry, ports of entry in smaller cities and towns are likely to play more important roles in expediting cross-border merchandise trade. To date, however, there has been very little formal analyses of the trade flows through many of these other, potentially key ports. This study attempts to partially fill part of that gap in the border economics literature by analyzing northbound cargo vehicle flows from Mexico to the United States through Ojinaga, Chihuahua and Presidio, Texas. Results indicate that the price of diesel fuel, United States business cycles, export manufacturing employment in Chihuahua City, and the inflation adjusted bilateral currency value of the peso influence the monthly volume of cargo trucks that use this border crossing facility.